Synthesis and structure-activity relationships of novel ecdysteroid dioxolanes as MDR modulators in cancer. - Amaral, Leonard (2021)
Ecdysteroids, molting hormones of insects, can exert several mild, non-hormonal bioactivities in mammals, including humans. In a previous study, we have found a significant effect of certain derivatives on the ABCB1 transporter mediated multi-drug resistance of a transfected murine leukemia cell line. In this paper, we present a structure-activity relationship study focused on the apolar dioxolane derivatives of 20-hydroxyecdysone. Semi-synthesis and bioactivity of a total of 32 ecdysteroids, including 20 new compounds, is presented, supplemented with their complete 1H- and 13C-NMR signal assignment.